English-Speaking Anxiety Among Second- and Fourth-Year Thai University English Majors - Cedar, Payung; Jaiyote, Suwimol (Journal of Community Development Research (Humanities and Social Sciences); Vol 17 No 4 (2024): October - December 2024, 2024)
This comparative study surveyed English speaking anxiety among second- and fourth-year English majors at a northern Thai university, examining factors contributing to anxiety and potential differences between the two groups. A five-point Likert scale questionnaire addressing the effects of communication apprehension, fear of assessment, and fear of negative evaluation, along with an open-ended question about other issues contributing to English-speaking anxiety, was administered online to 31 second- and 34 fourth-year students. The results showed that students in both groups experienced moderate levels of anxiety in terms of comprehension apprehension and test anxiety. However, there was a notable difference in the levels of fear of negative evaluation. Specifically, second-year English majors exhibited a high level of fear of negative evaluation while fourth-year English majors experienced it at a moderate level. Despite this, statistical analyses revealed significant differences between the two groups in all three core factors: comprehension apprehension ( t = -3.449, p < .05), test anxiety ( t = 2.920, p < .05), and fear of negative evaluation ( t = 10.711, p < .0001). Interestingly, although previous research suggests that more years of study generally reduce anxiety, this study found that this does not hold true across all factors. Additionally, analyses of anxiety levels across various scenarios revealed specific anxiety-inducing factors. Furthermore, the written responses predominantly highlighted grammar and vocabulary as areas of concern. These findings offer implications for pedagogical strategies and suggest avenues for future research. Keywords: Anxiety, Speaking, English, Thai Students, University